(untitled) (Journal of the College of Basic Education, 2019)
The problem of research is that there is a need to make different approaches to develop the learning process and improve the skill performance in this game and thus improve the skill performance of the class of learners and players.Therefore, the researcher considered providing an educational program for the triple overlap between the methods of scheduling exercise and knowing its effect on the development of skill performance and accuracy of scoring football for the halls. The study aimed to prepare an educational program based on the interplay between the random exercise method and the variable exercise method and the intensive exercise method that matches the capabilities of the research sample, as well as to identify the effect of the educational program in developing skill performance and accuracy of scoring for the sample of research in the game of football for the halls. The sample of the research was from the players of Balad Sports Club participating in the first division football league halls and the number (20) players divided into two groups one pilot and the other control and by (10) players for each group was applied educational program on the experimental group and the duration of its implementation (8) weeks (3) educational training units per week, and after processing the results statistically using statistical system SPSS researcher concluded that the proposed educational program has a positive impact on the development of skill performance and accuracy of scoring for football players of the halls and recommends the researcher should use the program Proposal.